Pendampingan Pemanfaatan Digital Branding dan Digital Marketing pada We Farm Hidroponik untuk Menuju Kawasan Agroeduwisata - Fitri Mailani; Eli Ratni; Danny Hidayat; Mulyanti Roberto Muliantino; Risti Kurnia Dewi; Virtous Setyaka (Warta Pengabdian Andalas, 2023)
"We Farm Hydroponics" is an agricultural business implementing a hydroponic system with the motto healthy vegetables and free of pesticides. The need for good business branding and proper digital marketing in advancing the "We Farm Hydroponic" business, especially in the field of marketing, so that it can be a solution to meet market needs and is well known by the public. The purpose of this activity is to provide assistance to partners in building business profiles/branding and digital marketing and to make "We Farm Hydroponics" a hydroponic agro-education area in West Sumatra; assistance to partners is carried out for three months starting from October to December 2022 with the method of mentoring, coaching, and development. The activities carried out were FGDs for the development of a hydroponic We Farm business into an agrotourism area, assistance in managing the legality of the "We Farm Hydroponics" business, namely the business registration number (NIB), fostering the development of the "We Farm Hydroponics" business to become an agrotourism area through strengthening branding/business profile. Assistance in optimizing promotions through digital marketing, training in maintaining the greenhouse area "We Farm Hydroponics," and training in hydroponic vegetable nutrition to improve the quality and quantity of hydroponic vegetable crops as well as training in making healthy food products made from hydroponic vegetables (vegetable juice and smoothies). This activity impacts increasing agrotourism visits to We Farm Hydroponics and increasing insight into We Farm Hydroponics' social media.